Aromatic thioether, polycarbonate prepared from thioether and application of polycarbonate

By introducing aromatic sulfide structures into polycarbonate, the problems of the existing high-refractive polycarbonate decrease in Abbe number and poor impact performance when increasing the refractive index, and achieve high refractive index, high impact strength and low doublet The refractive performance is improved and suitable for high-end optical lens applications.

CN119409606AActive Publication Date: 2025-02-11WANHUA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411528886.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

While the existing high-refractive polycarbonate increases the refractive index, the ABE number decreases, the material has poor impact performance at low temperatures, and the processing difficulty increases, which cannot meet the further improvement of performance of end customers.

Method used

Aromatic sulfide is used as polymerized monomers and polymerized with hydroxyl-containing compounds and carbonate diesters to prepare a polycarbonate material with high refractive index and high impact strength.

Benefits of technology

It improves the refractive index and impact strength of the material, reduces the birefractive index, improves the processing performance and sheeting rate, and meets the application needs of high-end optical lenses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409606A_ABST
    Figure CN119409606A_ABST
Patent Text Reader

Abstract

The invention relates to aromatic thioether, polycarbonate prepared from the thioether and application of the aromatic thioether, the aromatic thioether has the following structure: E1 is-CH (CH3) CH2-or-CH2CH2CH2-; and n is 8-20. The aromatic thioether provided by the embodiment of the invention can be used for preparing polycarbonate, and the prepared polycarbonate material has better refractive index and higher impact strength. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to polycarbonate, in particular to polycarbonate prepared by using aromatic sulfide and application thereof. Background Art

[0002] High-refractive polycarbonate (PC) is a special type of polycarbonate for optical lenses, which is prepared by melt transesterification polycondensation using fluorene and naphthalene dihydroxy compounds from the downstream of the coal tar deep processing industry chain as polymerization monomers. Its refractive index is usually greater than 1.60. Compared with other optical materials, high-refractive PC has a higher refractive index, low birefringence and good hydrothermal stability, and can be used in the field of high-end optical lenses, including mobile phone lenses, automotive lenses, security lenses, AR / VR glasses, drones, home smart cameras and other application scenarios.

[0003] The existing monomers for preparing high-refractive PC are mainly fluorene and naphthalene dihydroxy compounds. On the one hand, the refractive index of the material is limited, and on the other hand, while the refractive index is increased, the Abbe number will be significantly reduced. At the same time, because the material itself contains a large number of macrocyclic structures, it is prone to stress cracking and has poor impact performance at low temperatures, which limits its application in low-temperature places.

[0004] In addition, as the end customers' requirements for the performance of polycarbonate optical materials continue to increase, existing products cannot meet their needs. To increase the refractive index of the material, it is necessary to further increase the rigid ring in the material structure, which further enhances the rigid ring of the material. The increased rigid ring structure will further reduce the Abbe number of the material, affecting the user experience of the terminal. In addition, the strong polar carbonate bond also provides a large intermolecular force, which binds the molecular chains to each other, further improving the rigidity of the material and increasing the difficulty of processing. Summary of the invention

[0005] In order to overcome at least one defect of the above-mentioned prior art, in a first aspect, an embodiment of the present invention provides an aromatic sulfide having the following structure:

[0006]

[0007] Wherein, E1 is -CH(CH3)CH2- or -CH2CH2CH2-; n is 8 to 20.

[0008] In a second aspect, an embodiment of the present invention provides a polycarbonate, comprising a structural unit X derived from the above aromatic sulfide and a structural unit A and / or a structural unit B; wherein the structures of the structural unit X, the structural unit A, and the structural unit B are as follows:

[0009] Structural unit X:

[0010] Structural unit A:

[0011] Structural unit B:

[0012] wherein R1, R2, R3, and R4 are each independently selected from a hydrogen atom, a C1-C 20 Alkyl, C1~C 20 Alkoxy, C5~C 20 Cycloalkyl, C5~C 20 Cycloalkoxy, C6~C 20 Aryl, C6~C 20 of aryloxy.

[0013] In a third aspect, an embodiment of the present invention provides a method for preparing the above-mentioned polycarbonate, comprising reacting a hydroxyl-containing compound with a carbonate diester to perform a polymerization reaction to obtain the polycarbonate; wherein the hydroxyl-containing compound comprises the above-mentioned aromatic sulfide and compound A and / or compound B; the structures of the compound A and the compound B are as follows:

[0014] Compound A:

[0015] Compound B:

[0016] wherein R1, R2, R3, and R4 are each independently selected from a hydrogen atom, a C1-C 20 Alkyl, C1~C 20 Alkoxy, C5~C 20 Cycloalkyl, C5~C 20 Cycloalkoxy, C6~C 20 Aryl, C6~C 20 of aryloxy.

[0017] In a fourth aspect, an embodiment of the present invention provides a polycarbonate material, comprising the above-mentioned polycarbonate or the polycarbonate prepared by the above-mentioned preparation method.

[0018] In a fifth aspect, an embodiment of the present invention provides an optical device, comprising the polycarbonate described above or the polycarbonate prepared by the above preparation method.

[0019] In a sixth aspect, an embodiment of the present invention provides the use of the above-mentioned polycarbonate or the polycarbonate prepared by the above-mentioned preparation method as an optical material.

[0020] The aromatic sulfide according to one embodiment of the present invention can be used to prepare polycarbonate, and the prepared polycarbonate material has a better refractive index and higher impact strength. DETAILED DESCRIPTION

[0021] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions therein are essentially used as illustrations rather than to limit the present invention.

[0022] One embodiment of the present invention provides an aromatic sulfide having the following structure:

[0023]

[0024] Wherein, E1 is -CH(CH3)CH2- or -CH2CH2CH2-; n is 8 to 20.

[0025] In one embodiment, n in the aromatic sulfide structure may be 8-20, further may be 8-16, further may be 10-16, for example, n may be 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.

[0026] In one embodiment, E1 in the aromatic thioether structure is connected to the ortho or para position of the 2-hydroxyethoxy group on the benzene ring.

[0027] In one embodiment, the aromatic thioether is selected from the following structures:

[0028]

[0029] One embodiment of the present invention provides a method for preparing the above aromatic sulfide, comprising the following steps:

[0030] (1) reacting a phenol compound containing a double bond with sulfur to obtain an intermediate compound; and

[0031] (2) reacting the intermediate compound with ethylene oxide to obtain an aromatic sulfide;

[0032] Among them, the phenol compound containing a double bond has the following structure:

[0033]

[0034] E2 is allyl (-CH2CH=CH2) or isopropenyl (-C(CH3)=CH2).

[0035] In one embodiment, in the phenol compound containing a double bond, E2 is located at the ortho or para position to the hydroxyl group on the benzene ring.

[0036] In one embodiment, the phenol compound containing a double bond includes one or more of o-allylphenol, p-allylphenol, o-isopropenylphenol, and p-isopropenylphenol.

[0037] In one embodiment, the preparation reaction of the aromatic sulfide can be a prior art, for example, the reaction of step (1) can be carried out with reference to the method disclosed in the document "The use of elemental sulfur as an alternative feedstock for polymeric materials. Nat. Chem., 2013, 5, 518-524"; the reaction of step (2) can be carried out with reference to the method disclosed in the document "Study on the synthesis of high refractive index optical resin monomer phenyl diether fluorene, Contemporary Chemical Research, 2022, 24, 180-182".

[0038] In one embodiment, in step (1), the mass ratio of the phenol compound containing a double bond to sulfur can be 1:(0.5-8), and can further be 1:(1-4), for example, 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:5, 1:6, 1:7.

[0039] In one embodiment, the reaction temperature of step (1) may be 175-195°C, further may be 180-190°C, for example 185°C.

[0040] In one embodiment, the reaction time of step (1) can be 1 to 12 hours, and further can be 2 to 10 hours, such as 2.5 hours, 5 hours, 7.5 hours, or 9 hours.

[0041] In one embodiment, in step (2), the molar ratio of ethylene oxide to the intermediate compound may be 1:(0.4-0.5), and may further be 1:(0.43-0.47), for example 1:0.45.

[0042] In one embodiment, the reaction temperature of step (2) may be 60-90°C, further 65-85°C, for example 70°C, 75°C, 80°C.

[0043] In one embodiment, the reaction time of step (2) can be 3 to 8 hours, and further can be 4 to 6 hours, for example, 4.5 hours, 5 hours, 5.5 hours, or 7 hours.

[0044] In one embodiment, the reaction in step (2) is carried out under the action of a catalyst, and the catalyst may be sodium hydroxide.

[0045] In one embodiment, the molar ratio of the catalyst to ethylene oxide in step (2) is 0.05:(0.1-1), for example, 0.05:0.2, 0.05:0.3, 0.05:0.5, 0.05:0.8.

[0046] One embodiment of the present invention provides the use of the above aromatic sulfide in the preparation of polycarbonate.

[0047] One embodiment of the present invention provides a polycarbonate, comprising a structural unit X derived from the above aromatic sulfide and a structural unit A and / or a structural unit B; wherein the structures of the structural unit X, the structural unit A, and the structural unit B are as follows:

[0048] Structural unit X:

[0049] Structural unit A:

[0050] Structural unit B:

[0051] wherein R1, R2, R3, and R4 are each independently selected from a hydrogen atom, a C1-C 20 Alkyl, C1~C 20 Alkoxy, C5~C 20 Cycloalkyl, C5~C 20 Cycloalkoxy, C6~C 20 Aryl, C6~C 20 of aryloxy.

[0052] In one embodiment, the number of carbon atoms contained in the alkyl or alkoxy group of R1, R2, R3 or R4 can be 1 to 20, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.

[0053] In one embodiment, the number of carbon atoms contained in the cycloalkyl or cycloalkoxy group of R1, R2, R3 or R4 can be 5 to 20, for example 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.

[0054] In one embodiment, the number of carbon atoms contained in the aryl or aryloxy group of R1, R2, R3 or R4 may be 6 to 20, for example 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.

[0055] In one embodiment, R1, R2, R3, and R4 are each independently selected from a hydrogen atom, a C1-C3 alkyl group, a C6-C 12 The aromatic group.

[0056] In one embodiment, in structural unit A, R1 and R2 are both hydrogen atoms, or R1 and R2 are both phenyl groups.

[0057] In one embodiment, in structural unit B, R3 and R4 are both hydrogen atoms, or R3 and R4 are both phenyl groups.

[0058] In one embodiment, the polycarbonate includes structural units X and structural units A.

[0059] In one embodiment, the polycarbonate includes structural units X and structural units B.

[0060] In one embodiment, the polycarbonate includes structural unit X, structural unit A, and structural unit B.

[0061] In one embodiment, in the polycarbonate, the molar ratio of the structural unit X to the structural unit A and the structural unit B may be 1:0-99:0-99, and the molar numbers of the structural unit A and the structural unit B are not 0 at the same time; further, the molar ratio of the structural unit X to the structural unit A and the structural unit B may be 1:10-80:10-80.

[0062] In one embodiment, the molar ratio of structural unit A to structural unit B can be 1-18:1-4, for example, 1:1.7, 1:1.8, 1:2, 1:3, 1:3.5, 1.8:1, 2:1, 5:1, 10:1, 15:1.

[0063] In one embodiment, in the structural unit of the polycarbonate, the molar content of the structural unit X can be 4-10%, for example 4.5%, 4.7%, 4.8%, 5%, 5.5%, 6%, 7%, 8%, 9%. The above molar content is based on the sum of the moles of the structural unit X, the structural unit A, and the structural unit B.

[0064] In one embodiment, the weight average molecular weight of the polycarbonate can be 10,000 to 150,000, further can be 20,000 to 130,000, and further can be 30,000 to 120,000, for example, 11,000, 12,000, 30,000, 50,000, 60,000, 67,000, 68,000, 70,000, 90,000, 91,000, 95,000, 97,000, 98,000, and 100,000.

[0065] In one embodiment, the molecular weight distribution (PDI) of the polycarbonate may be 1.8 to 2.0, such as 1.83, 1.88, or 1.98.

[0066] In one embodiment, the hydroxyl content (or terminal hydroxyl content) of the polycarbonate is less than 1000 ppm, and may further be 300 to 500 ppm, wherein the hydroxyl groups are mainly derived from monomers corresponding to the structural unit X, the structural unit A and / or the structural unit B.

[0067] In one embodiment, the content of small molecule by-products in the polycarbonate product is less than 500 ppm, further 100-300 ppm.

[0068] One embodiment of the present invention provides a method for preparing the above-mentioned polycarbonate, comprising polymerizing a hydroxyl-containing compound with a carbonic acid diester to obtain the polycarbonate; wherein the hydroxyl-containing compound comprises the above-mentioned aromatic sulfide and compound A and / or compound B; the structures of compound A and compound B are as follows:

[0069] Compound A:

[0070] Compound B:

[0071] wherein R1, R2, R3, and R4 are each independently selected from a hydrogen atom, a C1-C 20 Alkyl, C1~C 20 Alkoxy, C5~C 20 Cycloalkyl, C5~C 20 Cycloalkoxy, C6~C 20 Aryl, C6~C 20 of aryloxy.

[0072] In one embodiment, the polymerization reaction of the hydroxyl-containing compound and the carbonic acid diester can be carried out using existing processes.

[0073] In one embodiment, the aforementioned definitions apply to R1, R2, R3, and R4.

[0074] In one embodiment, compound A is selected from one or two of the following compounds:

[0075]

[0076] In one embodiment, compound B is selected from one or two of the following compounds:

[0077]

[0078] In one embodiment, the molar ratio of aromatic sulfide to compound A and compound B may be 1:0-99:0-99, and the molar numbers of compound A and compound B are not 0 at the same time; further, the molar ratio of aromatic sulfide to compound A and compound B may be 1:10-80:10-80.

[0079] In one embodiment, the molar ratio of compound A to compound B can be 1-18:1-4, for example, 1:1.7, 1:1.8, 1:2, 1:3, 1:3.5, 1.8:1, 2:1, 5:1, 10:1, 15:1.

[0080] In one embodiment, the hydroxyl-containing compound includes 4 to 10 mol% of aromatic sulfide, and further, the molar content of aromatic sulfide in the hydroxyl-containing compound can be, for example, 4.5%, 4.7%, 4.8%, 5%, 5.5%, 6%, 7%, 8%, 9%. The above molar content is based on the molar number of the hydroxyl-containing compound.

[0081] In one embodiment, the molar ratio of the carbonic acid diester to the hydroxyl-containing compound may be (1-1.1):1, and further may be (1-1.05):1.

[0082] In one embodiment, the carbonic acid diester includes one or more of diphenyl carbonate, ditolyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, and dicyclohexyl carbonate. Further, the carbonic acid diester may be diphenyl carbonate and / or ditolyl carbonate.

[0083] In one embodiment, the carbonic acid diester and the hydroxyl-containing compound may be reacted in the presence of a catalyst or in the absence of a catalyst by a melt transesterification polycondensation method.

[0084] In one embodiment, the catalyst of the carbonic acid diester and the hydroxyl-containing compound reaction system can be selected from sodium hydroxide, sodium bicarbonate, magnesium hydroxide, cesium carbonate, calcium hydroxide, strontium hydroxide, barium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, trimethylbenzylammonium hydroxide, triethylamine, zinc acetate, zinc benzoate, 2-ethylhexanoic acid zinc, tin chloride, tin acetate, cerium acetylacetonate, zirconium acetylacetonate, zirconium acetate, tetrabutoxy zirconium One or more. Further, the catalyst is selected from sodium hydroxide, sodium bicarbonate, cesium carbonate, cerium acetylacetonate, zirconium acetate, zinc acetate One or more.

[0085] In one embodiment, the molar ratio of catalyst to carbonic acid diester can be 1×10 -8 ~1×10 -3 , which can be further 1×10 -6 ~1×10 -4 .

[0086] In one embodiment, the polymerization reaction of carbonic acid diester and hydroxyl-containing compound includes a material melting stage, an ester exchange stage and a polycondensation stage. Furthermore, the small molecular compounds generated during the reaction can be removed in real time by distillation.

[0087] In one embodiment, the temperature of the reaction system in the melting stage can be 100-250°C, further can be 140-200°C, for example 130°C, 135°C, 150°C, 160°C, 180°C; the insulation time can be 20-50 min, further can be 30-40 min.

[0088] In one embodiment, the pressure of the reaction system in the ester exchange stage can be 20-80 KPa (A), for example 30 KPa, 40 KPa, 60 KPa, 70 KPa; the reaction temperature can be 140-280 ° C, and can further be 170-250 ° C, for example 200 ° C, 220 ° C, 230 ° C, 235 ° C, 240 ° C, 260 ° C; the reaction time can be 30-180 min, and can further be 60-90 min, for example 70 min, 80 min.

[0089] In one embodiment, the pressure of the reaction system in the condensation stage can be 5-1000 Pa (A), and can further be 50-150 Pa (A), for example, 60 Pa, 80 Pa, 100 Pa, 120 Pa; the temperature can be 200-350 ° C, and can further be 250-300 ° C, for example, 240 ° C, 260 ° C, 265 ° C, 270 ° C, 280 ° C; the reaction time can be 5-90 min, and can further be 15-60 min, for example, 25 min, 30 min, 45 min.

[0090] One embodiment of the present invention provides a polycarbonate material, comprising the above-mentioned polycarbonate.

[0091] In one embodiment, the refractive index of the polycarbonate material (eg, film or sheet) at 23° C. and a wavelength of 589 nm is 1.70 to 1.75, such as 1.71, 1.72, 1.73, or 1.74.

[0092] In one embodiment, the Abbe number of the polycarbonate material is 15 to 20, for example, 15.5, 16, 16.5, 17, 17.5, 18, 18.5, 19, 19.5.

[0093] In one embodiment, the impact strength of the polycarbonate material is 50 to 65 J / m 2 , for example 51 J / m 2 、54J / m 2 、56J / m 2 、62J / m 2 .

[0094] In one embodiment, the light transmittance of the polycarbonate material is above 88%, and may further be 88-90%, such as 88.5% or 88.9%.

[0095] In one embodiment, the haze of the polycarbonate material is below 0.7%, further 0.3-0.7%, such as 0.33%, 0.35%, 0.4%, 0.45%, 0.6%, 0.65%, 0.67%.

[0096] One embodiment of the present invention provides an optical device, comprising the above-mentioned polycarbonate.

[0097] In one embodiment, the optical device may be an optical lens or an optical film.

[0098] In one embodiment, the optical device can be used in devices or equipment such as mobile phone lenses, vehicle lenses, security lenses, AR / VR glasses, drones, home smart cameras, etc.

[0099] One embodiment of the present invention provides the use of the above-mentioned polycarbonate as an optical material.

[0100] One embodiment of the present invention provides use of the above-mentioned polycarbonate in preparing an optical device.

[0101] In a polycarbonate or a material thereof according to an embodiment of the present invention, the presence of an aromatic sulfide structure enables the material to have high refractive index and high Abbe number, while increasing the toughness of the material and improving the processing characteristics of the material, thereby significantly improving the impact strength and film forming rate of the manufactured device.

[0102] The polycarbonate or material thereof according to one embodiment of the present invention contains an aromatic sulfide structure comprising a plurality of sulfur atoms. Compared with the monosulfide / disulfide structure, the presence of the aromatic sulfide structure increases the flexibility of the polymer, can prevent brittle cracking, and improves the processing performance of the material, thereby significantly improving the impact strength and sheeting rate of the material, and improving the refractive index of the material without losing the Abbe number; in addition, the aromatic sulfide structure can reduce the birefringence of the material, thereby improving the overall optical performance of the material.

[0103] The polycarbonate or its material in one embodiment of the present invention has the characteristics of high refractive index, high Abbe number and low birefringence, and is particularly suitable for the application of small-sized aspherical products such as optical lenses. In addition, since polycarbonate has a flexible thioether structure, it can greatly improve the phenomenon of cracks and the like occurring during the reprocessing of the product, meeting the use requirements of multi-lens lenses.

[0104] The preparation of polycarbonate according to one embodiment of the present invention is further described below with reference to examples. The raw materials and test methods involved in each example and comparative example are as follows.

[0105] raw material

[0106] Diphenyl carbonate: Shanghai Titan;

[0107] BPEF: Jiangsu Yongxing;

[0108] BPPF:Jiangsu Yongxing

[0109] BHEBN: Jiangsu Yongxing;

[0110] 2,2-Bis(2-hydroxyethoxy)-5,5-diphenyl-1,1-binaphthyl (BHEBBN): prepared according to the method disclosed in patent CN 114957954A.

[0111] Test Method

[0112] 1. Test of weight average molecular weight (Mw) and molecular weight distribution (PDI)

[0113] Gel permeation chromatography (GPC) was used with dichloromethane as the developing solvent and a calibration curve was prepared using standard polystyrenes of known molecular weight (molecular weight distribution = 1). Based on this calibration curve, Mw and PDI were calculated from the retention time of GPC.

[0114] 2. Refractive index (nD) test

[0115] The resin obtained in each example or comparative example was made into a plate with a thickness of 1 mm, and the refractive index (nD) of the resin plate was measured at 23° C. and a wavelength of 589 nm using an Abbe refractometer according to JIS-K-7142.

[0116] 3. Abbe number test

[0117] The refractive indices nF(486), nD(589), and nC(656) at wavelengths of 486 nm, 589 nm, and 656 nm at 23°C were measured using an Abbe refractometer, and the Abbe number ν was calculated using the following formula:

[0118] ν=(nD-1) / (nF-nC).

[0119] 4. Test of light transmittance and haze

[0120] The light transmittance and haze were measured using a turbidity meter according to the method of JIS-K-7361-1.

[0121] 5. Impact test

[0122] The notched Izod impact strength test was conducted in accordance with ASTM D256 in an environment with a temperature of 25° C. and a relative humidity of 50%. The testing machine model was Instron CEAST 9050.

[0123] 6. Orientation birefringence (Δn): Polycarbonate was made into a cast film with a thickness of 0.1 mm, and the cast film was cut into squares of 5.0 cm. Then, both ends of the film were inserted into chucks (3.0 cm between chucks), and stretched to 1.5 times at Tg+5°C of the polycarbonate resin. The phase difference (Re) at 589 nm was measured using an ellipsometer, and the orientation birefringence (Δn) was calculated using the following formula.

[0124] Δn=Re / d

[0125] Δn: orientation birefringence; Re: phase difference; d: thickness.

[0126] Preparation Example 1

[0127] The intermediate compound was prepared by reacting p-isopropenylphenol with sulfur (mass ratio of 1:1) at 195°C for 4 hours; and the intermediate compound (molar ratio of 1:0.45) was reacted with ethylene oxide at 70°C for 5.5 hours under the catalytic conditions of sodium hydroxide (molar ratio of catalyst to ethylene oxide of 1:4) to prepare the X1 compound, which has the following structural formula, wherein n is 8, referred to as "X1-8 compound". The elemental analysis results show that the sulfur content of the X1-8 compound is 40.9%.

[0128]

[0129] Preparation Example 2

[0130] The intermediate compound was prepared by reacting o-isopropenylphenol with sulfur (mass ratio of 1:4) at 175°C for 6 hours; ethylene oxide and the intermediate compound (molar ratio of 1:0.43) were reacted at 60°C for 7 hours under the catalytic conditions of sodium hydroxide (molar ratio of catalyst to ethylene oxide was 1:10) to obtain X2 compound, the structural formula of which is as follows, wherein n is 12, referred to as "X2-12 compound". The elemental analysis results show that the sulfur content of X2-12 compound is 52.1%.

[0131]

[0132] Preparation Example 3

[0133] The intermediate compound was prepared by reacting p-propylene phenol with sulfur (mass ratio of 1:8) at 195°C for 4 hours; ethylene oxide and the intermediate compound (molar ratio of 1:0.47) were reacted at 70°C for 4 hours under the catalytic conditions of sodium hydroxide (molar ratio of catalyst to ethylene oxide of 1:10) to obtain the X3 compound, the structural formula of which is as follows, wherein n is 16, referred to as "X3-16 compound". The elemental analysis results show that the sulfur content of the X3-16 compound is 58.9%.

[0134]

[0135] Preparation Example 4

[0136] The intermediate compound was prepared by reacting o-propylene phenol with sulfur (mass ratio of 1:2) at 175°C for 5 hours; ethylene oxide and the intermediate compound (molar ratio of 1:0.5) were reacted at 70°C for 3 hours under the catalytic conditions of sodium hydroxide (molar ratio of catalyst to ethylene oxide of 1:10) to prepare the X4 compound, the structural formula of which is as follows, wherein n is 10, referred to as "X4-10 compound". The elemental analysis results show that the sulfur content of the X4-10 compound is 47.2%.

[0137]

[0138] Comparative Preparation Example 1

[0139] (1) reacting phenol with disulfur dichloride to obtain the following intermediate compound: the molar ratio of phenol to disulfur dichloride is 2.1:1, reacting at 140° C. for 6 hours in the presence of an alkali metal hydroxide to obtain the following intermediate compound;

[0140]

[0141] (2) reacting ethylene oxide with the intermediate compound obtained in step (1): the molar ratio of ethylene oxide to the intermediate compound is 1:0.5, reacting at 80° C. for 6 hours to obtain the following disulfide compound.

[0142]

[0143] Example 1

[0144] 0.033 mol BPEF, 0.059 mol BHEBN, 0.005 mol X1-8 compound, 0.1 mol diphenyl carbonate, 5.0×10 -7mol of sodium hydroxide was added to the reactor. Nitrogen was replaced 3 times, heated to 132°C at normal pressure, and kept for 30 minutes. When the raw materials were completely melted, stirring was started; the pressure was adjusted to 40KPa(A), the temperature was raised to 235°C, by-products began to distill out, and the reaction was maintained for 80 minutes; then the temperature was raised to 250°C, the pressure was reduced by program, and the pressure was gradually reduced to 80Pa(A) within 1 hour, and the reaction was terminated for 30 minutes.

[0145] The obtained polycarbonate was taken out and the performance was tested according to the above method. The results are shown in Table 1.

[0146] After the polycarbonate was vacuum dried at 120°C for 8 hours, it was injection molded using a SE30DU injection molding machine manufactured by Sumitomo Heavy Industries, Ltd. The molding temperature was Tg+110°C and the mold temperature was Tg-10°C. A spherical lens with a thickness of 0.2mm, a convex curvature radius of 5mm, a concave curvature radius of 4mm, and a diameter of 5mm was obtained. The film forming rate was 97.3%.

[0147] Example 2

[0148] 0.021 mol BPEF, 0.069 mol BHEBBN, 0.009 mol X2-12 compound, 0.1 mol diphenyl carbonate, 4.0×10 -7 1 mol of tetrabutylammonium hydroxide was added to the reactor. Nitrogen was replaced 3 times, heated to 180°C at normal pressure, and kept for 30 minutes. When the raw materials were completely melted, stirring was started; the pressure was adjusted to 60KPa(A), the temperature was raised to 220°C, the by-product began to distill out, and the reaction was maintained for 60 minutes; then the temperature was raised to 240°C, the pressure was reduced by program, and the pressure was gradually reduced to 100Pa(A) within 1 hour, and the reaction was terminated for 45 minutes.

[0149] The obtained polycarbonate was taken out and the performance was tested according to the above method. The results are shown in Table 1.

[0150] The polycarbonate was made into a spherical lens by the same method as in Example 1, and the film formation rate was 97.3%.

[0151] Example 3

[0152] 0.09 mol BPPF, 0.005 mol BHEBN, 0.004 mol X3-16 compound, 0.1 mol diphenyl carbonate, 5.0×10 -61 mol of tin acetate was added to the reactor. Nitrogen was replaced 3 times, heated to 160℃ at normal pressure, and stayed for 30 minutes. When the raw materials were completely melted, stirring was started; the pressure was adjusted to 30KPa(A), the temperature was raised to 250℃, and the by-product began to distill out, and the reaction was maintained for 80 minutes; then the temperature was raised to 300℃, and the pressure was reduced by program, and the pressure was gradually reduced to 100Pa(A) within 1 hour, and the reaction was terminated for 15 minutes.

[0153] The obtained polycarbonate was taken out and the performance was tested according to the above method. The results are shown in Table 1.

[0154] The polycarbonate was made into a spherical lens by the same method as in Example 1, and the film formation rate was 98.3%.

[0155] Example 4

[0156] 0.06 mol BPPF, 0.03 mol BHEBBN, 0.005 mol X4-10 compound, 0.1 mol diphenyl carbonate, 1.0×10 -6 1 mol of tin acetate was added to the reactor. Nitrogen was replaced 3 times, heated to 200℃ at normal pressure, and stayed for 20 minutes. When the raw materials were completely melted, stirring was started; the pressure was adjusted to 70KPa(A), the temperature was raised to 260℃, the by-product began to distill out, and the reaction was maintained for 90 minutes; then the temperature was raised to 265℃, the pressure was reduced by program, and the pressure was gradually reduced to 80Pa(A) within 1 hour, and the reaction was terminated for 25 minutes.

[0157] The obtained polycarbonate was taken out and the performance was tested according to the above method. The results are shown in Table 1.

[0158] The polycarbonate was made into a spherical lens by the same method as in Example 1, and the film formation rate was 96.3%.

[0159] Comparative Example 1

[0160] This example uses substantially the same raw materials and process as Example 1 to prepare polycarbonate, with the only difference being that an equal molar amount of BPEF is used to replace the X1-8 compound.

[0161] The obtained polycarbonate was taken out and the performance was tested according to the above method. The results are shown in Table 1.

[0162] The polycarbonate was made into a spherical lens by the same method as in Example 1, and the film formation rate was 87.3%.

[0163] Comparative Example 2

[0164] This example uses substantially the same raw materials and process as Example 2 to prepare polycarbonate, with the only difference being that an equal molar amount of BPEF is used to replace the X2-12 compound.

[0165] The obtained polycarbonate was taken out and the performance was tested according to the above method. The results are shown in Table 1.

[0166] The polycarbonate was made into a spherical lens by the same method as in Example 1, and the film formation rate was 73.3%.

[0167] Comparative Example 3

[0168] This example uses substantially the same raw materials and process as Example 3 to prepare polycarbonate, with the only difference being that an equal molar amount of BPPF is used to replace the X3-16 compound.

[0169] The obtained polycarbonate was taken out and the performance was tested according to the above method. The results are shown in Table 1.

[0170] The polycarbonate was made into a spherical lens by the same method as in Example 1, and the film formation rate was 79.3%.

[0171] Comparative Example 4-1

[0172] This example uses substantially the same raw materials and process as Example 4 to prepare polycarbonate, with the only difference being that an equimolar amount of BHEBBN is used to replace the X4-10 compound.

[0173] The obtained polycarbonate was taken out and the performance was tested according to the above method. The results are shown in Table 1.

[0174] The polycarbonate was made into a spherical lens by the same method as in Example 1, and the film formation rate was 77.7%.

[0175] Comparative Example 4-2

[0176] This example uses substantially the same raw materials and process as Example 4 to prepare polycarbonate, with the only difference being that the disulfide compound of Comparative Preparation Example 1 is substituted for the X4-10 compound in an equimolar amount.

[0177] The obtained polycarbonate was taken out and the performance was tested according to the above method. The results are shown in Table 1.

[0178] The polycarbonate was made into a spherical lens by the same method as in Example 1, and the film formation rate was 82.7%.

[0179] Table 1

[0180]

[0181] According to the description of each embodiment and comparative example, the difference between embodiment 1 and comparative example 1, embodiment 2 and comparative example 2, embodiment 3 and comparative example 3, embodiment 4 and comparative example 4-1 is that comparative examples 1, 2, 3, and 4-1 do not use aromatic sulfide to prepare polycarbonate. Referring to the results in Table 1, it can be seen that compared with comparative examples 1, 2, 3, and 4-1, the polycarbonate materials prepared in embodiments 1, 2, 3, and 4 have higher refractive index, impact strength, and lower birefringence, and the film formation rate of the prepared spherical lens is also higher. Therefore, by introducing an aromatic sulfide structure into polycarbonate, the above-mentioned properties of the material are improved.

[0182] Further, the difference between Example 4 and Comparative Example 4-2 is that the disulfide compound used in Comparative Example 4-2 contains only two sulfur atoms, while the X4-10 compound used in Example 4 contains 10 sulfur atoms. Referring to the results in Table 1, it can be seen that the polycarbonate material prepared in Example 4 has better refractive index, impact strength and production rate than those in Comparative Example 4-2. Therefore, compared with aromatic compounds containing two sulfur atoms, the use of aromatic sulfides containing multiple sulfur atoms to prepare polycarbonate can further improve the refractive index, impact strength and production rate of spherical lenses of the material.

[0183] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.

[0184] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.

Claims

1. An aromatic sulfide having the following structure: in, E1 is -CH(CH3)CH2- or -CH2CH2CH2-; n is 8-20.

2. The aromatic sulfide according to claim 1, which is selected from the following structures: And / or, n is 8 to 16.

3. A polycarbonate comprising a structural unit X derived from the aromatic sulfide according to claim 1 or 2 and a structural unit A and / or a structural unit B; wherein: The structures of the structural unit X, the structural unit A, and the structural unit B are as follows: Structural unit X: Structural unit A: Structural unit B: wherein R1, R2, R3, and R4 are each independently selected from a hydrogen atom, a C1-C 20 Alkyl, C1~C 20 Alkoxy, C5~C 20 Cycloalkyl, C5~C 20 Cycloalkoxy, C6~C 20 Aryl, C6~C 20 of aryloxy.

4. The polycarbonate according to claim 3, wherein R1, R2, R3, and R4 are each independently selected from a hydrogen atom, a C1-C3 alkyl group, a C6-C 12 and / or, The molar ratio of the structural unit X to the structural unit A and the structural unit B is 1:0-99:0-99, and the molar numbers of the structural unit A and the structural unit B are not 0 at the same time; or, Based on the sum of the molar numbers of the structural unit X, the structural unit A and the structural unit B, the molar content of the structural unit X is 4-10%; and / or, The weight average molecular weight of the polycarbonate is 10,000 to 150,000; and / or, The terminal hydroxyl content of the polycarbonate is less than 1000 ppm.

5. The polycarbonate according to claim 3, wherein R1, R2, R3, R4 are each independently selected from a hydrogen atom, a phenyl group; and / or, The molar ratio of the structural unit X to the structural unit A and the structural unit B is 1:10-80:10-80; and / or, The weight average molecular weight of the polycarbonate is 20,000 to 130,000; and / or, The terminal hydroxyl content of the polycarbonate is 300 to 500 ppm.

6. The method for preparing the polycarbonate according to any one of claims 3 to 5, comprising reacting a hydroxyl-containing compound with a carbonic acid diester to carry out a polymerization reaction to prepare the polycarbonate; wherein: The hydroxyl-containing compound comprises the aromatic sulfide according to any one of claims 1 to 3 and compound A and / or compound B; the structures of compound A and compound B are as follows: Compound A: Compound B: wherein R1, R2, R3, and R4 are each independently selected from a hydrogen atom, a C1-C 20 Alkyl, C1~C 20 Alkoxy, C5~C 20 Cycloalkyl, C5~C 20 Cycloalkoxy, C6~C 20 Aryl, C6~C 20 of aryloxy.

7. The preparation method according to claim 6, wherein: The compound A is selected from one or two of the following compounds: The compound B is selected from one or two of the following compounds: and / or, The carbonic acid diester includes one or more of diphenyl carbonate, ditolyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, and dicyclohexyl carbonate; and / or, The hydroxyl-containing compound includes 4 to 10 mol % of the aromatic sulfide.

8. A polycarbonate material, comprising the polycarbonate according to any one of claims 3 to 5 or the polycarbonate prepared by the preparation method according to claim 6 or 7. 9 . An optical device, comprising the polycarbonate according to claim 3 , or the polycarbonate prepared by the preparation method according to claim 6 or 7 .

10. Use of the polycarbonate according to any one of claims 3 to 5 or the polycarbonate prepared by the preparation method according to claim 6 or 7 as an optical material.

Citation Information

Patent Citations

  • Thiol and sulfur-containing O-(meth) acrylate compound and use thereof

    CN1173490A

  • Novel sulfurized phenolic resin, process for producing the same, phenol derivative having thioether structure or disulfide structure, process for producing the same, and epoxy resin composition and ad

    CN1625577A

  • Aromatic polycarbonate resin composition

    US20040147655A1

  • Copolycarbonate and optical lens

    US20110298143A1